2009
DOI: 10.1093/eurheartj/ehp063
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of persistent atrial fibrillation ablation using termination as a procedural endpoint

Abstract: Procedural termination of long-lasting AF by catheter ablation alone is associated with an improved outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
258
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(278 citation statements)
references
References 34 publications
12
258
2
Order By: Relevance
“…The outcomes of the stepwise ablation approach have also been reported in three additional patient series from the same group 34,35,37 . Sacher et al 37 enrolled 43 persistent/long-standing persistent AF patients (AF mean 11 months, ranging from 1 month to 6 years) who underwent the same extensive ablation procedure.…”
Section: Stepwise Ablation Approachmentioning
confidence: 92%
See 2 more Smart Citations
“…The outcomes of the stepwise ablation approach have also been reported in three additional patient series from the same group 34,35,37 . Sacher et al 37 enrolled 43 persistent/long-standing persistent AF patients (AF mean 11 months, ranging from 1 month to 6 years) who underwent the same extensive ablation procedure.…”
Section: Stepwise Ablation Approachmentioning
confidence: 92%
“…Five studies have reported the clinical success associated with the stepwise ablation approach for persistent/long-standing persistent AF [34][35][36][37][38] . Haissiguerre and colleagues described the stepwise ablation approach in 60 persistent/long-standing persistent AF patients with regards to critical structures for acute AF slowing or termination and long term clinical outcome 38 .…”
Section: Stepwise Ablation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recent advances in mapping, ablation of AF "substrate" was synonymous with extensive lesions, with variable results 19,[60][61][62] and damage to atrial function 63 . One perceptible trend is to perform less extensive AF ablation, because widespread ablation may increase complications and reduce atrial function 63 , from the disappointing efficacy of extensive ablation of complex fractionated electrograms 19,61,62 and from mechanistic trends to identify targets amenable to localized ablation lesions.…”
Section: Trends In Mechanistic Understanding To Improve Ablation Of Afmentioning
confidence: 99%
“…Laboratories using this approach reported high long term success rate in up to 88% without anti-arrhythmic drugs despite the need for multiple procedures due to recurrent atrial tachycardias. [3][4][5][6] Specifically, from a prospective study of 153 consecutive patients, O'Neill and co-workers demonstrated that 95% of those with AF termination remained in sinus rhythm at a mean follow-up duration of 32 months as compared to just 52% in those without AF termination following repeat ablation procedures. 6 Likewise, in a smaller series of 88 patients by Rostock et al the overall success rate was 95% in those with as compared to 5% in those without termination of AF in two procedures and a mean follow-up duration of 20 months.…”
Section: Introductionmentioning
confidence: 99%